The periphery as the centre: trajectories of responsibility and community support in contemporary Maputo, Mozambique - Oppenheim, Beth T (Department of Environmental and Geographical Science, 2017)
Development researchers have long held a belief that developed states use their power to provide Aid or other forms of external assistance such as private philanthropy, assistance of Non-Governmental Organisations, and other private financing to underdeveloped, or developing, nations to achieve global economic and political stability. Development scholars (including geographers) have largely attributed this to a sense of responsibility. Many have assumed this assistance to travel in one direction, i.e. from Global North to Global South, thus overlooking the modalities of care and hospitality among individuals within countries of the Global South. In this thesis, I posit that looking at everyday modes of assistance at the community level would challenge scholars to re-think the ways in which place matters in development. Analysing qualitative data gathered through interviews and focus groups in two neighbourhoods in Maputo, Mozambique, this study is ultimately an investigation of proximity. I argue that the closeness of people in these complex community relationships matters in three ways: (i) the everyday practices of assistance in these communities are modes of resistance to an oppressive state; (ii) forms of assistance serve as expressions of local (as opposed to national) identity; and (iii) religious institutions play a significant role in fostering public discourse, rather than motivating assistance itself. In speaking more specifically about how proximity matters, this study contributes uniquely to the growing realisation that development must come from within.